2016
DOI: 10.3892/ol.2016.4554
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the ataxia telangiectasia mutated pathway for effective therapy against hirsutine-resistant breast cancer cells

Abstract: Abstract. The present authors have recently demonstrated that hirsutine, one of the major alkaloids in Uncaria species, promotes cell apoptosis by inducing DNA damage and suppresses metastasis of breast cancer cells. Despite its potent anti-cancer activity, certain types of human breast cancer cells exhibit resistance to hirsutine. To maximize the clinical utility of hirsutine therapy against breast cancer, it is critical to explore the underlying mechanism that protects hirsutine-resistant breast cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A recent study found that HSN causes mitochondrial death by causing ATP depletion, the formation of ROS, the loss of mitochondrial membrane potential, and the discharge of cytochrome C (Cyt C) [ 34 ]. Additionally, to overcome HSN resistance, it may be helpful to disrupt the ataxia telangiectasia mutated (ATM) pathway, which results in ROS production and a p53-independent DNA damage response in breast cancer cells [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study found that HSN causes mitochondrial death by causing ATP depletion, the formation of ROS, the loss of mitochondrial membrane potential, and the discharge of cytochrome C (Cyt C) [ 34 ]. Additionally, to overcome HSN resistance, it may be helpful to disrupt the ataxia telangiectasia mutated (ATM) pathway, which results in ROS production and a p53-independent DNA damage response in breast cancer cells [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to a study by Meng et al (2021), HCN showed cytotoxicity against Jurkat clone E6-1 tumor cells [ 25 ]. In a different study, it was discovered that HSN exhibits strong cytotoxicity against human breast cancer cell lines, including MCF-7, MDA-MB-231, MCF-10A, BT474, and MDA-MB-453 with concentrations ranging from 6.25−160 M ( Table 3 ) [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we focused on 2 cancer‐predisposing genes, ATM and BMI‐1, in association with breast cancer. The involvement of ATM and BMI‐1 in carcinogenesis is biologically plausible . ATM is an acronym for ataxia telangiectasia mutated.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of ATM and BMI-1 in carcinogenesis is biologically plausible. [15][16][17][18] ATM is an acronym for ataxia telangiectasia mutated. ATM is a serine/threonine kinase involving in DNA damage repair, cell arrest and apoptosis, and chromatin remodelling.…”
mentioning
confidence: 99%